2015
DOI: 10.2514/1.b35530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Injector Geometry on Cryogenic Shear Coaxial Jets at Supercritical Pressures

Abstract: For shear coaxial injectors, which are widely used in liquid oxygen-gaseous hydrogen rocket engines, the key parameters that characterize injector geometry are the recess length, taper angle, and wall thickness of the liquid oxygen post, which is the inner tube of the coaxial injector. In the present study, the effects of the recessed length and taper angle of the liquid oxygen post on cryogenic coaxial jets at supercritical pressures were experimentally investigated. The large-scale structure and mixing enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Figure 6 shows the relationship between the self-excited oscillation frequency of the jet and the injection conditions. It can be found that the self-excited oscillation frequency of the jet increases significantly as the distance of the nozzle from the cyclone increases, which is consistent with the phenomenon found in coaxial nozzles [10]. As the injection pressure increases, the momentum difference between the rotating gas and kerosene decreases, and the oil-gas interaction weakens, making the jet more stable.…”
Section: Effect Of Injection Parameters On the Frequency Of Self-exci...supporting
confidence: 84%
“…Figure 6 shows the relationship between the self-excited oscillation frequency of the jet and the injection conditions. It can be found that the self-excited oscillation frequency of the jet increases significantly as the distance of the nozzle from the cyclone increases, which is consistent with the phenomenon found in coaxial nozzles [10]. As the injection pressure increases, the momentum difference between the rotating gas and kerosene decreases, and the oil-gas interaction weakens, making the jet more stable.…”
Section: Effect Of Injection Parameters On the Frequency Of Self-exci...supporting
confidence: 84%
“…In general, J is believed to represent the forces that govern the primary breakup of the LOX jet in shear coaxial injectors [23][24][25]. Higher values of J indicate enhanced the mixing processes between oxidizer and fuel [26].…”
Section: Resultsmentioning
confidence: 99%
“…The momentum flux ratio (J-number) plays an important role in models describing the forces which govern the primary breakup of the LOX jet in shear coaxial injectors [18][19][20]. Higher values of J enhance the mixing processes between oxidizer and fuel [21]. Thus, the influence of the momentum flux ratio, calculated according to Equation ( 5), on the flame anchoring mechanism will be investigated.…”
Section: Resultsmentioning
confidence: 99%